1998
DOI: 10.1143/jpsj.67.3867
|View full text |Cite
|
Sign up to set email alerts
|

Off-Diagonal Wave Function Monte Carlo Studies of Hubbard Model I

Abstract: We propose a Monte Carlo method, which is a hybrid method of the quantum Monte Carlo method and variational Monte Carlo theory, to study the Hubbard model. The theory is based on the off-diagonal and the Gutzwiller type correlation factors which are taken into account by a Monte Carlo algorithm. In the 4×4 system our method is able to reproduce the exact results obtained by the diagonalization. An application is given to investigate the half-filled band case of two-dimensional square lattice. The energy is fav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 25 publications
0
68
0
Order By: Relevance
“…Then we can apply the standard Monte Carlo sampling method to evaluate the expectation values. 16,35 In order to perform a search for optimized values of the parameters included in the wave functions, we employ a correlated-measurements method to reduce the cpu time needed to find the most descendent direction in the parameter space. 36 In one Monte Carlo step all the Hubbard-Stratonovich variables are updated once following the Metropolis algorithm.…”
Section: 35mentioning
confidence: 99%
See 1 more Smart Citation
“…Then we can apply the standard Monte Carlo sampling method to evaluate the expectation values. 16,35 In order to perform a search for optimized values of the parameters included in the wave functions, we employ a correlated-measurements method to reduce the cpu time needed to find the most descendent direction in the parameter space. 36 In one Monte Carlo step all the Hubbard-Stratonovich variables are updated once following the Metropolis algorithm.…”
Section: 35mentioning
confidence: 99%
“…The purpose of this paper is to investigate the effect of hole doping in the ground state of the three-band Hubbard model in the underdoped region using a variational Monte Carlo method [14][15][16] which is a tool to control the correlation from weakly to strongly correlated regions. It is shown that the AF long-range ordering disappears due to extra holes doped into the two-dimensional plane.…”
Section: Introductionmentioning
confidence: 99%
“…We choose to demonstrate our scheme on the modified Gutzwiller wave function (GWF) defined as 33,34 |Ψ G = e −hKP G |Φ = e −hK e −β in i↑ni↓ |Φ .…”
Section: Methods a The Gutzwiller Wave Functionmentioning
confidence: 99%
“…The ground state energy is lowered appreciably by the introduction of λ [11]. This type of wave function is an approximation to the wave function in quantum Monte Carlo method [22][23][24].…”
Section: Optimized Wave Functionmentioning
confidence: 99%
“…The CuO 2 plane in cuprates plays a key role for the appearance of superconductivity [2][3][4][5][6][7][8][9][10] and the electron correlation in this plane is important [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%